Snowmen at Christmas - Buehner, Caralyn; Buehner, Mark (New York : Dial Books for Young Readers, 2005)
On Christmas Eve, snowmen hold a party in the center of town and celebrate with food, music and dancing, and presents.
Sequel to: Snowmen at night.
Accelerated Reader AR
Keywords: Snowmen -- Juvenile fiction; Christmas stories; Parties -- Juvenile fiction; Stories in rhyme